Sistem Informasi Pelayanan Terintegrasi Berbasis Web pada Kecamatan Wewewa Timur - Febriami Lende; Yulius Nahak Tetik; Karolus Wulla Rato (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Wewewa Timur District is an administrative area in Southwest Sumba Regency that has great potential to improve the quality of public services. However, in practice, services at the sub-district level are still faced with various obstacles, such as slow administrative processes, manual data recording, and lack of coordination between service departments. This makes it difficult for government officials to cause problems and has a direct impact on public satisfaction as service recipients. As a solution, the development of a Web-Based Integrated Service Information System is the right step to address community needs and support government performance in Wewewa Timur District. Through this system, the public can access various services on a single digital platform without having to come directly to the sub-district office, and helps officials in accelerating administrative processes. This study uses a software engineering approach to design and implement a Web-Based Integrated Service Information System in Wewewa Timur District. The method used is the Waterfall method, which is a classic method in software engineering with sequential and systematic stages, from needs analysis to system maintenance. Test results using the black box method showed that the software could identify malfunctioning functions, interface errors, data structure errors, and access to external databases, while also producing expected output. Therefore, this system is considered effective in improving the quality of public services in Wewewa Timur District.